Analisis Komparatif Kinerja Keuangan Perusahaan Sektor Energi Sebelum dan Sesudah Implementasi Kebijakan Energi Hijau - Tabah Rizki; Nurul Syahbela (Jurnal Penelitian Ekonomi Akuntansi, 2025)
This study aims to comparatively analyze the financial performance of energy sector companies before and after the implementation of the green energy policy in Indonesia in 2022, as part of the national commitment to transition toward clean energy. The research employs a comparative quantitative approach using financial ratio analysis, including Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), and Current Ratio (CR), for energy companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2024 period. The results of the comparative statistical tests using the Paired Sample t-Test and descriptive analysis indicate significant changes in most financial performance indicators following the adoption of the green energy policy. ROA and ROE increased significantly, reflecting improved efficiency and profitability, while DER decreased significantly, indicating a shift toward a healthier and more sustainable capital structure. Meanwhile, CR increased but was not statistically significant. These findings align with legitimacy theory, which explains that companies seek to obtain and maintain social legitimacy by aligning their policies and strategies with external environmental expectations. The implications suggest that the green energy policy plays a crucial role in strengthening corporate legitimacy in the eyes of the public and stakeholders, enhancing investor confidence, and supporting long-term financial sustainability. The limitations of this study lie in the relatively short observation period (2022–2024), which may not fully capture the long-term effects of the green energy policy on financial performance, and in the exclusive focus on financial indicators without considering non-financial factors such as governance quality, green investment intensity, and clean technology adoption. Future research is recommended to extend the observation period to five or ten years to capture long-term impacts, integrate quantitative and qualitative approaches through sustainability report analysis, ESG policy evaluation, and investor perception studies, and conduct cross-subsector comparisons to provide deeper insights into adaptation dynamics and competitiveness within the energy industry under the green energy transition toward a sustainable economy.